KKN PPM diversifikasi olahan ikan laut di Desa Pancana Kabupaten Barru - Ernawati S. Kaseng; Pince Salempa; Abdul Rahman (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The more advanced technology that humans use in their lives, it does affect behavior and lifestyle, including food consumption problems. Along with the increase of public income, consumption of fish products have been increased in both fresh fish and especially processed fish in a modern day. Barru District especially in Pancana village is one of the potential areas in the field of maritime and fisheries. Area of sea fishing and ponds around 56,160 Ha, pond 2,570 Ha beach 1,400 ha and pond cultivation area or freshwater 39 Ha. While the current fishery production is: shrimp (633.01 tonnes); Milkfish (, 552.08 tons); Cakalang/Cob (260.6 tonnes); Grouper/Snapper (744 tons); Red fish (97.02 tonnes); and seaweed (251.07 tons) that have been tested and are good enough. In the sub-district of Tanete Rilau Barru, several groups of fishermen, the village of its members cultivate milkfish and shrimp windu in ponds, ponds and cages using the technique of heavy water pond and in the rice fields (the system of Mina Padi and brackish). This is possible with the source of water originating from the location of natural waterfalls and baths in Tanete Riaja Sub-district located in the region. Given the potential, the development of seawater fish in this region has been developed by farmers or fishermen in recent years.